FETTLING OF UNITS OF THE METAL BOTTOM BLOWING OF BLAST STEEL-FURNACE - M. A. Murikov; A. I. Nosovets; V. M. Nosovets; A. V. Olenchenko; I. I. Shkulkova (Литьë и металлургия)
The research work on unification of the units fettling of the metal bottom blowing with inert gas is carried out on the arc steel furnaces No 1, 2, 3.